Experiment and numerical simulation study on the bionic tubes with gradient thickness under oblique loading. (June 2021) - Song, Jiafeng; Xu, Shucai; Zhou, Jianfei; Huang, Han; Zou, Meng
Abstract: A class of bionic gradient thickness (BGT) tubes with 2 cross-sectional shapes (circle and rectangle) are proposed. The energy absorption and deformation modes of four thin-walled tubes, including a bionic circular tube (BCT), and a bionic rectangle tube (BRT) with gradient thickness, and the counterpart uniform-thickness (UT) tubes, namely circular tube (CT) and rectangle tube (RT), are analyzed by Ls-Dyna. Before detailed analysis, the simulation and bionic design are verified by quasi-static experiments, which show that the BCT has better deformation than the CT, and the experimental curves also are well consistent with the simulation. The BCT has a better energy absorption capacity when subjected to different oblique loading angles. The selection and parameterization of sample points are studied based on full-factor tests. The design factors significantly affect the specific energy absorption (SEA) and peak force (PF) of the BCT under multi-angle oblique loading. Finally, the multi-objective optimization design considering the load angle is conducted to obtain the optimal design of the BCT. The optimum BCT has a 9.3% higher SEA compared with CT. Moreover, there is a mass reduction of 4% than the CT. Highlights: Series of bionic gradient thickness tubes were designed inspired by bamboo. Crashworthiness of bionic tubes under variable oblique impact loads were analyzed. The bionic structure is verified by experiments and theoretical models. Bionic structural parameters had an effect on their crashworthiness. Bionic structures were optimized by response surface optimization method.